Microcontroller based SMPS protection - Khairi, Khalib (2008)
This project have 3 main objectives to achieve, first the project should be able to protect DC load equipment from over voltage from their maximum voltage value or lower voltage from their minimum value. Second it should be able to protect DC load equipment from over current form their maximum current value or lower current from their minimum value. Third the voltage and current protection value are free to set by user. Simple methodology for this project is when the protection circuit detects any high or low voltage and current from power supply output that supplied to the load, it will stop the Pulse-width modulation (PWM) signal output. Sensing circuit will detect any voltage and current alteration output from power supply. Using the PIC microcontroller (PIC 18F4550), it will control the PWM signal output. The PWM output signal can be use for the power supply switching circuit. If the PWM signal stops, the operation for the power supply also will stop. Controlling the PWM signal will ensure that we can control the power supply whether want to turn it on or off.